Construction: Notes on Qualitative Time and Space - Pacheco, José Antón (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The conceptual definition of time and space has given rise to some difficulties in classical philosophy. These difficulties worsen with reference to time, which is presented as an «obscure idea». The root of the problem lies in considering time and space exclusively as measurable realities. Time and space are not only quantitative, but are also qualitative, and this fact has repercussions in various areas of life.